Uso de probióticos em doenças autoimunes gastrointestinais: uma revisão sistemática - Friedrich, Jennifer Alexandra Castanho Vieira (2020)
Probiotics affect the intestinal microbiota, stimulating immunological and nonimmunological mechanisms of the intestinal mucosa through antagonism with a potential pathogen. In autoimmune diseases, the immune system attacks and harms the body itself, and many of these diseases affect the gastrointestinal system. The objective of this work was to evaluate the use of probiotic bacteria in the treatment of autoimmune diseases through a systematic review of in vivo studies conducted in patients with autoimmune diseases of the gastrointestinal system (autoimmune gastritis; inflammatory bowel diseases: Crohn's disease and ulcerative colitis; celiac disease and autoimmune enteropathy). Thus, a systematic review was carried out in the following databases: Pubmed, Cochrane Library, Scopus and Web of Science using advanced search strategies. Data management was performed using Microsoft Office Excel and EndNote. 2868 articles were retrieved, and after screening duplicate articles and evaluating the abstracts regarding the eligibility criteria, 47 articles were selected for the development of the systematic review. Among the selected articles, the majority were related to ulcerative colitis, with 81.08% with a beneficial outcome regarding the use of probiotics, whereas with Crohn's disease, only 55.56% had a positive outcome. Regarding celiac disease, 85.71% demonstrate a beneficial effect in the use of probiotics. No articles were selected regarding autoimmune gastritis and autoimmune enteropathy. After evaluating the articles, it is suggested that the intervention with probiotics has benefits in the treatment of celiac disease along with a gluten-free diet. Regarding IBDs, it is suggested that the ingestion of probiotics also has benefits in patients with ulcerative colitis, however, it is not possible to conclude the beneficial effect in the use of probiotics in Crohn's disease.